High school students' modeling abilities in arithmetic sequences using body weight contexts - Rosanti, Aprida; Aisyah, Nyimas; Darmawijoyo, Darmawijoyo; Lestari, Siti; Utami, Lintang Fitra (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Mathematical modeling is an important skill in mathematics education, helping students use math to solve real-world problems. Teaching and assessing this skill can be challenging, especially when students need to apply algebraic concepts in their models.Aim: This study aims to assess the ability of high school students to model mathematical problems related to weight changes using arithmetic sequences. The focus is on how well students can understand the problem, identify relevant mathematical concepts, apply these concepts, and explain their results.Method: The study involved 28 high school students who were given two open-ended modeling tasks. A qualitative descriptive approach was used to analyze how students performed in four key stages of mathematical modeling: understanding the problem, identifying mathematical concepts, applying mathematical procedures, and explaining the results.Results: The results showed that 79% of the students reached the minimum proficiency level in mathematical modeling. Students performed very well in understanding the problem (94.05%) and identifying relevant mathematical concepts (90.48%), but had more difficulty in applying these concepts, especially in algebraic calculations (71.43%). This suggests that more attention is needed in teaching algebra within modeling tasks.Conclusion: The study highlights the benefits of using real-world contexts to improve students' mathematical modeling skills. However, it also points out the need to strengthen students' understanding of algebra to help them apply mathematical concepts more effectively. Integrating more mathematical modeling into the curriculum could better prepare students to solve complex real-world problems.